Leukemia detection from blood smears - Htike@Muhammad Yusof, Zaw Zaw (2014)
Leukemia is a highly fatal hematologic cancer which starts in blood-forming tissue, such as bone marrow and triggers high production of immature and abnormal shaped blood cells. Skilled medical officers or microbiologists are required to diagnose leukemia from blood smears. This poses a problem in remote areas and rural areas where there is a shortage of qualified medical personnel. This paper proposes a computer-aided diagnosis system that can detect and classify leukemia from blood microscopic images. Satisfactory preliminary experimental results demonstrate the efficacy of our system.